2006
DOI: 10.1016/j.eururo.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum A Toxin Intravesical Injections in the Treatment of Painful Bladder Syndrome: A Pilot Study

Abstract: e u r o p e a n u r o l o g y 4 9 ( 2 0 0 6 ) 7 0 4 -7 0 9 a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e u r o p e a n u r o l o g y . c o m Article info AbstractObjective: We evaluated the efficacy and tolerability of botulinum A toxin (BTX-A) intravesical injections in patients affected by painful bladder syndrome with increased urinary frequency, refractory to conventional treatment modalities. Methods: Twelve women and two men were prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(37 citation statements)
references
References 25 publications
2
32
0
3
Order By: Relevance
“…Although infection, autoimmune response, allergic reaction, neurogenic inflammation, and epithelial dysfunction mechanisms have been suggested in etiology, there is no general consensus on the physiopathology of the disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although infection, autoimmune response, allergic reaction, neurogenic inflammation, and epithelial dysfunction mechanisms have been suggested in etiology, there is no general consensus on the physiopathology of the disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…[177][178][179][180][181] Two small, double-blind RCTs have been conducted. Manning et al found no significant overall difference between patients randomized to HD plus NS injection vs. HD plus 500 U Dysport ® .…”
Section: Botulinum Toxin a (Btx-a) (Option Grade C)mentioning
confidence: 99%
“…It has been well documented that intramural bladder BoNT-A injections suppress urgency in patients with neurogenic and idiopathic bladder overactivity, and the use of BoNT-A has recently been expanded to include the treatment of IC/PBS [23,24]. A number of experimental studies in rodents have provided evidence that the sensory effects of BoNT-A might be a consequence of suppression of afferent signaling.…”
Section: Discussionmentioning
confidence: 97%